Needs Analysis of Google Sites to Reduce Cognitive Load in Three-Variable Linear Equation Systems - Chajar Ero; Irwan Akib; Nasrun Nasrun (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
The material of Three-Variable Linear Equation Systems (TVLES) possesses high complexity that potentially causes excessive cognitive load for students. This research is a preliminary study aimed at analyzing students' learning difficulties and mapping the requirements for developing digital learning media to reduce this cognitive load. Specifically, this study addresses two research questions: (1) which TVLES sub-skills are the most difficult and what types of errors dominate? and (2) what media feature preferences are prioritized by students and teachers? The research method employed is a descriptive quantitative-qualitative (mixed-methods) approach to provide a comprehensive overview of the subjects' conditions. The research subjects consisted of 24 tenth-grade students at SMA Negeri 13 Gowa who had completed the TVLES material in the 2024/2025 academic year. Data collection techniques utilized source triangulation, including student needs analysis questionnaires, grade document analysis, in-depth interviews, and student work error analysis using conceptual, procedural, and computational coding frameworks. The results indicated low student learning outcomes, with a class average of 68.96 and a classical mastery rate of only 33.3%. Identified difficulties were consistent with indicators of cognitive overload, particularly the inability to model word problems (88%), indicating excessive information load on working memory. Based on preference analysis, 95.8% of students stated the necessity of developing Google Sites-based media containing step-by-step explanatory videos. The research concludes that the identified design requirements suggest the development of Google Sites as a strategic direction with the potential to reduce extraneous cognitive load and facilitate independent learning.